Reinventing the Wheel.
To prevent rollover accidents, new cars sold in the United States since 2004 have been outfitted with tire-pressure monitors that warn the driver when tires are going flat. But the battery-powered initial version of the technology has proved expensive. A consortium of tire manufacturers hopes to cut the cost. It's testing a sensor embedded in the tires that needs no battery and can radio pressure data from the tire to electronics inside the car. The secret is a cheap, coin-size device called a PZT bimorph that harvests energy from the tire's motion via a miniature piezoelectric springboard. The tire makers are working with EoPlex Technologies, in Redwood City, Calif., which has tuned its three dimensional printing technology to construct the kilometers of wiring in today's cars.
Keywords: Battery powered version; Radio pressure data; Sensor embedded; Tire pressure monitors; Wheel